Teaching of technological courses by means of learning styles applied to statistics (Research, Society and Development, 2018)
The present work aims to answer the question about what is the influence of the knowledge of statistics in the learning about Occupations and Salaries for students of a Higher Course of Technology in Human Resources Management in a Private Education Institution of the city of São Paulo? In order to answer this question, the following general objective was established: to analyze basic statistical knowledge used in the classroom in the study on salary research and, specifically, to understand the learning styles of the students, proposing actions aligned to the profile of these students. In terms of methodology, this article has a qualitative approach, in an exploratory-descriptive order, since it aims to obtain definitions, descriptions, expositions and information about a circumstance, identifying the present relations between the factors that compose it and the subjects involved. In spite of the qualitative nature, the ILS (Index of Learning Styles) questionnaire, by Felder and Soloman (1991), was also used to classify the learning styles of the subjects involved in the work and to determine the learning styles of the subjects. two classes worked.